High-intensity interval training increasing ADP-ribosylation factor 6 and Cytochrome C in visceral adipose tissue of male Wistar rats. (June 2019) - Rahmati, Masoud; Shariatzadeh, Mohammad; Kazemi, Abdolreza; Taherabadi, Seyed Jalal
Abstract : Background: High-intensity interval training (HIIT) can be related to the beneficial adaptations in adipose tissue even though its underlying mechanisms have not yet been clarified. Considering the significant effect of ADP-ribosylation factor 6 (ARF6) and Cytochrome C (CytC, as a marker of mitochondrial content) on adipose tissue plasticity, it was proposed that the positive impacts of high-intensity interval training (HIIT) on visceral adipose tissue (VAT) might be mediated by ADP-ribosylation factor 6 (AEF6) and Cytochrome C (CytC). To examine the research hypothesis, the effect of 6-week high-intensity interval training (HIIT) on ADP-ribosylation factor 6 (ARF6) and Cytochrome C (CytC) protein levels in visceral adipose tissue (VAT) of male Wistar rats was evaluated. Methods: A total number of 12 male Wistar rats were randomly divided into two groups: control (C) and trained (high-intensity interval training: HIIT) wherein the trained group was exposed to 6 weeks of high-intensity interval running. The ADP-ribosylation factor 6 (ARF6) and Cytochrome C (CytC) protein expressions were also assessed by immunohistochemistry (IHC) analyses. Moreover, independent sample t -test was used to compare between-group differences and the significance level was determined by p ≤ 0.05. Results: The immunohistochemistry (IHC) analyses showed that protein levels of ADP-ribosylation factor 6 (ARF6) and Cytochrome C (CytC) were significantly higher in the group receiving high-intensity interval training compared with the control group after 6 week (p = 0.018 & p = 0.0001, respectively). Conclusions: The increased levels of ADP-ribosylation factor 6 (ARF6) and Cytochrome C proteins due to high-intensity interval training could be related to improved metabolism and glucose homeostasis. It was also suggested to take the physiological consequences of this adaptation into account in future studies.